OPTIMALISASI PARIWISATA KAWASAN SUKUH DAN CETO KABUPATEN KARANGANYAR DENGAN MENGGALI POTENSI SENI TRADISI - Santosa - (Institut Seni Indonesia Surakarta, 2016)
The article is the result of the research entitled â€œThe optimalization of tourism in Sukuh and Ceto areas, Kabupaten Karanganyar by increasing the potency of traditional art as a means of creative economic developmentâ€. The research aimed at making a model for developing an integrated tourism in Sukuh and Ceto areas which could be empowered as a an effort at increasing public economy and at strengthening local culture. A two-year research was carried out to attain the goal. The results of the first stage research are as follows: many kinds of art have been identified completely and comprehensively; a plan of developing art for tourism which can have an effect on economic development of the local society has been known; the model of art created is based on the approach of art for tourism with the following characteristics: an imitation of the original, compressed